Faustmann and the Climate - Michael Hoel; Bjart Holtsmark; Katinka Holtsmark (Statistics Norway, Research Department, 2012)
This paper presents an adjusted Faustmann Rule for optimal harvest of a forest in the presence of a social cost of carbon emissions. A contribution of the paper is to do this within theoretical and numerical frameworks that take account of the dynamics and interactions of the forest's multiple carbon pools within an infinite time horizon model. With our less restrictive assumptions we find that a social cost of carbon has a significantly stronger effect on the optimal harvest age than found in earlier studies. Considered is also how increased use of harvest residues for energy purposes and storage of carbon in building materials and furniture should influence the length of the rotation period. The theoretical results are quantified within a numerical framework.
Keywords: Q23; Q54; Q42; 330; climate; forestry; biofuels; Faustmann; carbon.